Investigation into Electrical Energy Consumption in ABU Samaru Zaria - Ede, Godwin Egbudu; Ishaya-Waidung, Zamani; Kamtu, Peter Mu’ar; Gukop, Nicholas Sylvester (ABUAD Journal of Engineering Research and Development (AJERD), 2023)
This work centers on the study of the electrical energy consumption pattern of Ahmadu Bello University Samaru Zaria over a period of five years to establish the present energy demand and to project future demand. To obtain the amount and pattern of electrical energy consumption, statistical data for five years were collected for Kaduna Electricity Distribution Company (KEDC) supply and generator supplement. These data were analyzed and forecast of future demand made based on the analysis. The study found out that due to power outages from KEDC, the University had to supplement KEDC supply by installing 7.74 MW capacity Diesel and Petrol generators in both academic and residential areas. The power supplied by these generators constitute 42.6% of monthly energy consumption in 2018, 40% in 2019, 39% in 2020, 49.3% in 2021, 55.27% in 2022 and 37.3% as at May 2023. Some methods to reduce energy waste are recommended and sources other than fossil fuel Powered generators are suggested for future supplement of supply from KEDC.